(untitled) (Proceedings of the International Conference on Social Sciences, 2022)
Historically, witch-hunting is a form of gender-based violence targeting mostly women and driven by societal prejudices. Metaphorically, during the COVID-19 pandemic witch-hunting has come to connote targeted discrimination and violence driven by social prejudices about the disease. People from different groups, communities, and occupations have been the targets of the latter. Simultaneously, although not as frequently, the same people have been the target of hero-welcoming for their role in fighting the spread and consequences of the disease. These incidents seem to confirm that in times of crisis and great uncertainty, people may behave in contradictory ways. They may look for scapegoats to vent their frustrations, worries, and fears based on their prejudices. They may also make heroes of those that provide calm, care, and courage based on their benevolent prejudices. The two opposing dynamics must be managed to minimize their ill-effects and maximize their good effects. The paper presents an ontological framework to understand the antecedents and consequences of the acts, and to manage them effectively. The study aims to propose a way forward to address the issue with the help of the ontological review of the relevant secondary literature.